Sustainable value chains for rangeland restoration and livelihoods in Africa—A tentative mapping - Wane, Abdrahmane (International Livestock Research Institute, 2023)
A presentation on sustainable value chains in rangelands in Africa made at GEF-funded STELARR project meeting on a global rangelands data platform, developed by ILRI and partners.